2015
DOI: 10.1155/2015/796249
|View full text |Cite
|
Sign up to set email alerts
|

Sample Preparation and Extraction in Small Sample Volumes Suitable for Pediatric Clinical Studies: Challenges, Advances, and Experiences of a Bioanalytical HPLC-MS/MS Method Validation Using Enalapril and Enalaprilat

Abstract: In USA and Europe, medicines agencies force the development of child-appropriate medications and intend to increase the availability of information on the pediatric use. This asks for bioanalytical methods which are able to deal with small sample volumes as the trial-related blood lost is very restricted in children. Broadly used HPLC-MS/MS, being able to cope with small volumes, is susceptible to matrix effects. The latter restrains the precise drug quantification through, for example, causing signal suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The applied liquid chromatography-tandem mass spectrometry methods were accurate, precise, and not affected by a matrix effect. 24 A recent publication using a comparable study design and method of detection to this study demonstrated maximum plasma concentrations of enalapril and enalaprilat, following 10 mg of a standard enalapril tablet, to be 58 ng/mL and 41 ng/mL, which are similar to 61 ng/mL and 48 ng/mL in this study. 23 Time to maximum concentration and AUC 0-Ý were also similar.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The applied liquid chromatography-tandem mass spectrometry methods were accurate, precise, and not affected by a matrix effect. 24 A recent publication using a comparable study design and method of detection to this study demonstrated maximum plasma concentrations of enalapril and enalaprilat, following 10 mg of a standard enalapril tablet, to be 58 ng/mL and 41 ng/mL, which are similar to 61 ng/mL and 48 ng/mL in this study. 23 Time to maximum concentration and AUC 0-Ý were also similar.…”
Section: Discussionsupporting
confidence: 80%
“…However, all drug concentrations in the presented study were determined by a validated bioanalytical assay in compliance with EMA and US FDA guidance on bioanalytical method validation. The applied liquid chromatography‐tandem mass spectrometry methods were accurate, precise, and not affected by a matrix effect …”
Section: Discussionmentioning
confidence: 99%
“…Determinations for enalapril, enalaprilat, aldosterone, renin, plasma renin activity and angiotensin I were performed at the institute or by an external partner (Spranger Laboratories, Ingolstadt, Germany). Drug concentrations of enalapril and its metabolite (enlaprilat) were determined using a low-volume LC/MS-MS method [ 21 ], whereas humoral parameters (aldosterone, renin, plasma renin activity and angiotensin I) were determined using enzyme-linked immunosorbent assays (ELISA) [ 22 , 23 ] or radioimmunoassays (RIA). The bioanalysis at the laboratories was performed blinded.…”
Section: Methodsmentioning
confidence: 99%
“…The use of liquid chromatography coupled to mass spectrometry (LC–MS/MS) offers a tool to quantify sensitively and targeted drugs and metabolites. Even if LC–MS/MS methods suitable for the detection of enalapril, enalaprilat and carvedilol have been developed for paediatric demands, 23,24 to our knowledge, no bioanalytical method is available to simultaneously assess enalapril, carvedilol and their metabolites. However, this is paramount to ensure safe and evidence‐based pharmacotherapy in children suffering from heart failure.…”
Section: Introductionmentioning
confidence: 99%